Pengaruh Penerapan Manajemen Risiko Terhadap Kinerja Keuangan Pada Bank Mega Syariah - Anisa Husna Adinta (2021)
This research shown to get informations, overview, and find out the effect of Risk Management on financial performance in Bank Mega Syariah. The population of this study using report from Bank Mega Syariah. This study using quarterly report data from 2017 - 2020 as the sample. The writer of this research using quantitative method with Multiple regression Analisys with IBM SPSS Statistics 26 version. The results showed that credit risk had a significant positive effect on financial performance, liquidity risk did not have a significant negative effect on financial performance, and credit risk and liquidity risks simultaneously positively influence financial performance in Bank Mega Syariah. This is indicated by the smaller the financing risk, the smaller the non-performing financing at Bank Mega Syariah. So, the financial performance of Bank Mega Syariah becomes healthy and can also generate profits from the use of assets owned by Bank Mega Syariah.